2013
DOI: 10.1007/s10461-013-0671-1
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of Smartphone Application-Based HIV Prevention Among Young Men Who Have Sex With Men

Abstract: Young men who have sex with men (YMSM) are increasingly using mobile smartphone applications (“apps”), such as Grindr, to meet sex partners. A probability sample of 195 Grindrusing YMSM in Southern California were administered an anonymous online survey to assess patterns of and motivations for Grindr use in order to inform development and tailoring of smartphone-based HIV prevention for YMSM. The number one reason for using Grindr (29%) was to meet “hook ups.” Among those participants who used both Grindr and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
150
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(169 citation statements)
references
References 50 publications
(50 reference statements)
12
150
1
3
Order By: Relevance
“…59,60 The San Francisco Department of Public Health successfully used online advertising for free syphilis testing at non-clinic sites. 61 Similarly, Grindr and other social media have been successfully used to advertise syphilis testing among MSM in Darwin, Australia and home-based selfcollection HIV testing in England.…”
Section: Existing and Anticipated Challenges Of The Sti Epidemic In Msmmentioning
confidence: 99%
“…59,60 The San Francisco Department of Public Health successfully used online advertising for free syphilis testing at non-clinic sites. 61 Similarly, Grindr and other social media have been successfully used to advertise syphilis testing among MSM in Darwin, Australia and home-based selfcollection HIV testing in England.…”
Section: Existing and Anticipated Challenges Of The Sti Epidemic In Msmmentioning
confidence: 99%
“…There are a broad range of different potential users for mhealth systems who will want these systems to communicate effectively with them, providing them with the specific information they need and using language and examples that they can relate to [3,27]. For example, research shows that mHealth systems have been designed for older and younger health care consumers, users with different education levels, people with different sexual orientations, people with drug and alcohol addictions, people from different minority and ethnic groups, people from different countries, including those who speak different languages, all of whom are likely to have different communication preferences and skills [14,[20][21][22][23]30,44,48]. It will be important for mHealth system designers to conduct audience analysis research to evaluate the literacy levels of different mHealth users to determine the best ways to communicate effectively with these groups [2,3].…”
Section: Resultsmentioning
confidence: 99%
“…There has also been a great deal of evidence that mHealth has been used effectively to promote consumers' adoption of healthy behaviors and reduction of unhealthy behaviors [11], including the following behavioral health issues: consumer adherence with treatment recommendations and prescribed medications [14,18], reducing risky sex behaviors and adopting safer sex strategies [23,41], increasing physical activity and exercise [9,30], maintaining healthy diets [22,47], tobacco control [1,53] drug and alcohol abuse reduction [20,39,44], and promoting screening behaviors for early detection of serious health problems [13,18,33]. Furthermore, evidence suggests that mHealth applications have the potential to improve health care delivery performance and retention of community health workers [24].…”
Section: The Promise Of Mhealthmentioning
confidence: 99%
“…In recent years, geosocial networking applications have become a primary way to identify sex partners among YMSM. 23 The Healthy Young Men's study, a longitudinal cohort study among US YMSM, found that the Internet was the most common way that study participants found their last sexual partners. 24 One YMSM study in Los Angeles found that two-thirds of respondents who used Grindr reported using the smartphone application to meet a sex partner.…”
Section: Increasing Access To Sex Partners During Travel Through Onlimentioning
confidence: 99%